Avaliação quantitativa da produção pesqueira artesanal de Anomalocardia brasiliana em um estuário do Rio Grande do Norte - Silva, Ciro José Fernandes (Universidade Federal Rural do Semi-Árido, 2015)
The aim of the study was to evaluate the effect of variables that influence the capture, in terms of biomass,of Anomalocardia brasiliana from the artisanal fisheries in Rio Grande do Norte estuary. For this accompaniments of production were conducted during the years 2007-2011. The variables tested in the preparation of the production model were as follows: year, month and salinity. It was observed that only these three variables were responsible for explanation of 22% of the total variance that influences the gross production of seafood. This initial result corroborates for creation and implementation of management plans for the shellfish fishery in the area
Evaluation of fishing craft production quantity in Anomalocardia brasiliana in a estuary of Rio Grande do Norte
Keywords: GAM; Marisqueiros; Pescaria de moluscos; GAM; Shellfish; Fishery of molluscs; CIENCIAS AGRARIAS::ZOOTECNIA::PRODUCAO ANIMAL